Three-Dimensional Brain Images in Preterm Children With Periventricular Leukomalacia - Hsiao-Feng Chou; Ming-Fan Lin; Chia-Yuan Chen; Ein-Yiao Shen (Pediatrics and Neonatology)
To investigate the use of three-dimensional (3D) brain magnetic resonance imaging (MRI) to evaluate in preterm children with periventricular leukomalacia. Materials and Methods: Semiautomated 3D classification of the gray and white tissues was used to reconstruct brain images of patients with confirmed periventricular leukomalacia from 2D MRI. Results: We studied 14 preterm patients. The gestational age ranged from 25–37 weeks. The corrected age ranged from 5–49 months. We reconstructed the gray matter, white matter, and ventricles in order to analyze the brain volume. Conclusion: Three-dimensional MRI is a good tool that can be used to demonstrate brain lesions in stereo and differentiate the gray matter, white matter, and ventricles. Brain volume can also be accurately evaluated.